Phenylnaphthalic anhydrides from water hyacinth (Pontederia crassipes Mart.) - Costa, Mayra F. [UNESP]; Luiz, Mayara M. [UNESP]; de Souza, Leonardo C. [UNESP]; Tempone, Andre G.; Lago, João Henrique G.; Nascimento, Isabele R. [UNESP] (Elsevier, 2021)
Nineteen compounds were isolated from the aerial parts and roots of Pontederia crassipes Mart. [≡ Eichhornia crassipes (Mart.) Solms] (Pontederiaceae), including the new 4-hydroxy-5-phenyl-1,8-naphthalic anhydride (1) and 4-hydroxy-5-(4-hydroxyphenyl)-1,8-naphthalic anhydride (2). In addition, chemically related phenylnaphthalic acid derivatives 1a and 2a were obtained. The structures of the compounds were established by 1D and 2D NMR and ESI-HRMS analysis. 8-Phenylphenalenones 3 and 4 were evaluated for antiprotozoal activity against trypomastigote forms of Trypanosoma cruzi and displayed moderate activity.
Keywords: Eichhornia crassipes; Phenylnaphthalic anhydrides; Phenylphenalenones; Pontederia crassipes; Pontederiaceae; Trypanosoma cruzi